The Pengaruh Terapi Healing Garden Terhadap Tingkat Kecemasan Pasien Rawat Inap Di Rumah Sakit Panti Nugroho Pakem - Yuliati, Agnes; Oktri Hastuti, Agustina Sri; Rina Setyani, Fransisca Anjar (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Backround : Healing garden is a natural therapy facility for patients by presenting a natural atmosphere so that the patient can interact with the natural surroundings with the aim of making the patient feel comfartable, relaxed, optimistic and excited. Patients who are hospitalized are one of the groups thar are prone to experiencing anxiety. The exixtence of a garden in the hospital environment is expected to be a supporting factorin helping the patient’s healing process. Keywords : healing garden terapy, anxiety level,